Trophic Role of the Tetrodotoxin-Bearing Flatworm Plancera multitentaculata in the Marine Food Web - Kyoko Shirai; Masaaki Ito; Takuto Yamamoto; Megumi Morimura; Inori Watanabe; Maho Kashitani; Shusuke Takizawa; Yui Kaneko; Kotone Nagahama; Anzu Hayashi; Taiki Okabe; Hikaru Oyama; et al. (Marine Biotechnology, 2026)

Three-dimensional microphysical structure of the lower positive charge region in a thunderstorm: A case study for a supercell observed using dual-polarization radars - Akihito Umehara; Satoru Yoshida; Syugo Hayashi; Shingo Shimizu; Namiko Sakurai; Hiroshi Yamauchi; Hanako Inoue; Nobuhiro Nagumo; Yukari Shusse (Atmospheric Research, 2025)

Reliable intraoperative diagnostic methods for PCNSL: utility of combining intraoperative immunohistochemistry, cytology, and flow cytometry in achieving optimal treatment - Akihiro Inoue; Yukihiro Miyazaki; Hideaki Watanabe; Masahiro Nishikawa; Kosuke Kusakabe; Takanori Ohnishi; Mashio Taniwaki; Takatsugu Honda; Takuya Kondo; Shingo Kinnami; Eiji Katayama; Seiji Shigekawa; et al. (Acta Neurologica Belgica, 2025)

Correction: Impacts of regime shift on the fishery ecosystem in the coastal area of Kyoto prefecture, Sea of Japan, assessed using the Ecopath model - Hiroshi Inoue; Shingo Watari; Hideki Sawada; Edouard Lavergne; Yoh Yamashita (Fisheries Science, 2024)

Systematic comparison of Mg K-edge XANES spectra of magnesium-bearing clay minerals and magnesium silicate hydrates: A promising tool for identifying magnesium silicate hydrate in natural samples - Kosuke Inoue; Yuto Nishiki; Keisuke Fukushi; Reo Suma; Tsutomu Sato; Hiroshi Sakuma; Kenji Tamura; Shingo Yokoyama; Misato Shimbashi; Tomoyuki Mizukami; Kensuke Unami; Yohei Noji; et al. (Applied Clay Science, 2023)

Impacts of regime shift on the fishery ecosystem in the coastal area of Kyoto prefecture, Sea of Japan, assessed using the Ecopath model - Hiroshi Inoue; Shingo Watari; Hideki Sawada; Edouard Lavergne; Yoh Yamashita (Fisheries Science, 2023)
The present study assessed the impact of regime shifts on the ecosystems that support fisheries in the coastal area of Kyoto Prefecture, the Sea of Japan. Ecopath models were constructed during cold (1985) and warm (2013) regime periods, when the fishery structures were different. Both models evaluated by pre-balance diagnostics were reliably constructed. Multiple ecosystem indicator values were compared between the two periods to assess changes in the ecosystem structure and the impact of fisheries on the ecosystem. The major change in catches in the coastal area of Kyoto Prefecture between 1985 and 2013 was that the Japanese sardine drastically declined and Spanish mackerel increased. The primary production requirements of fisheries ( %PPR ) were higher in 1985, reflecting the greater impact of sardine. The mean trophic level of catch and system omnivory index suggested that stability of trophic network increased after the sharp decline in sardine biomass. The %PPR, the loss of secondary production due to fisheries exploitation and probability analysis of fishery sustainability suggested that the fishery structure in 2013, which was dominated by set nets, contributed to a more sustainable fishery than the structure in 1985, when fishery was dominated by purse seines and set nets.

A survey on social jetlag in Japan: a nationwide, cross-sectional internet survey - Yoko Komada; Isa Okajima; Shingo Kitamura; Yuichi Inoue (Sleep and Biological Rhythms, 2019)

Antithrombotic Protein Filter Composed of Hybrid Tissue-Fabric Material has a Long Lifetime - Yusuke Inoue; Tomoyuki Yokota; Tsuyoshi Sekitani; Akiko Kaneko; Taeseong Woo; Shingo Kobayashi; Tomokazu Shibuya; Masaru Tanaka; Hiroyuki Kosukegawa; Itsuro Saito; Takashi Isoyama; Yusuke Abe; et al. (Annals of Biomedical Engineering, 2017)

The effect of comorbidity of restless legs syndrome and migraine on sleep and mood: an integration of multicenter data - Keisuke Suzuki; Masayuki Miyamoto; Tomoyuki Miyamoto; Shiho Suzuki; Yuichi Inoue; Momoyo Murata; Kentaro Matsui; Shingo Nishida; Kenichi Hayashida; Akira Usui; Yoichiro Ueki; Masaki Nakamura; et al. (Sleep and Biological Rhythms, 2016)

Genetic divergence of Chikungunya virus plaque variants from the Comoros Island (2005) - Caroline Wasonga; Shingo Inoue; Cecilia Rumberia; George Michuki; James Kimotho; Juliette R. Ongus; Rosemary Sang; Lillian Musila (Virus Genes, 2015)

The effect of light and temperature on the growth and photosynthesis of Gracilariopsis chorda (Gracilariales, Rhodophtya) from geographically separated locations of Japan - Ryuta Terada; Shingo Inoue; Gregory N. Nishihara (Journal of Applied Phycology, 2013)

Development of microsatellite markers for the endangered grassland species Vincetoxicum pycnostelma (Apocynaceae) by using next-generation sequencing technology - Naoyuki Nakahama; Shingo Kaneko; Azusa Hayano; Yuji Isagi; Miho Inoue-Murayama; Tohru Tominaga (Conservation Genetics Resources, 2012)

An overview on chlorophylls and quinones in the photosystem I-type reaction centers - Shunsuke Ohashi; Tatsuya Iemura; Naoki Okada; Shingo Itoh; Hayato Furukawa; Masaaki Okuda; Mayumi Ohnishi-Kameyama; Takuro Ogawa; Hideaki Miyashita; Tadashi Watanabe; Shigeru Itoh; Hirozo Oh-oka; et al. (Photosynthesis Research, 2010)

Unique regulation of glyoxalase I activity during osmotic stress response in the fission yeast Schizosaccharomyces pombe: neither the mRNA nor the protein level of glyoxalase I increase under conditions that enhance its activity - Yoshifumi Takatsume; Shingo Izawa; Yoshiharu Inoue (Archives of Microbiology, 2005)

Identification of thermostable glyoxalase I in the fission yeast Schizosaccharomyces pombe - Yoshifumi Takatsume; Shingo Izawa; Yoshiharu Inoue (Archives of Microbiology, 2004)

Fluctuation in the distribution of low‐salinity water in the North Equatorial Current and its effect on the larval transport of the Japanese eel - Shingo Kimura; Takashi Inoue; Takashige Sugimoto (Fisheries Oceanography, 2001)
Surface water in the North Equatorial Current (NEC) is composed of southern low‐salinity water diluted by precipitation to less than 34.2 psu and northern, high‐salinity tropical water greater than 34.8 psu. Analyses of 27‐year historical data, observed in winter and summer along the longitude 137°E by the Japan Meteorological Agency, shows that an obvious salinity front (34.5 psu) generated by the two water masses was usually located around 15°N. However, the salinity front has been moving northward during the past three decades. El Niño/Southern Oscillation (ENSO) affected salinity in the surface layer, while temperature changed in the middle layer. The salinity front sometimes moved southward, mainly south of 5°N, and the movement was well correlated with the southern oscillation index (SOI). Because precipitation at Yap (9.5°N, 138.1°E) fluctuated with SOI, this spike‐like southward movement of the salinity front was probably affected by reduction of low‐salinity water during El Niño in the north‐western Pacific Ocean. However, ENSO only induced such large southward movements of the salinity front when the time lag between the low precipitation and low SOI was short (within four months). This salinity front is quite important for long‐distance migrating fish such as the Japanese eel because the eels spawn just south of the salinity front in the NEC. This behaviour suggests that the movement of the salinity front associated with ENSO may control the success of larval transport from the spawning ground in the NEC to the nursery ground in East Asia. In fact, catch of the Japanese eel larvae in Japan was well correlated with fluctuation of SOI and the location of the salinity front, and lower catch occurred during El Niño. The salinity front has moved from 13°N to 17°N during the past three decades. Considering that conditions of larval transport are worse north of 15°N, we suggest that decadal‐scale linear decrease of glass eel catch during the past three decades also can be explained by the displacement of the salinity front.